Gene flow between crops and their wild relatives - Andersson, Meike S.; Vicente, M. Carmen de (2010)
The work summarizes both state-of-the-art knowledge and research gaps related to gene flow and introgression between crops and their wild relatives. The information is based on a comprehensive review of the relevant scientific and technical literature. It emphasizes gene transfer from GM crops to wild species, rather than between different cultivars (i.e., from GM to conventional varieties) of the same crop. The 20 crop chapters are divided into the following sections: * General biological information (crop's scientific name, its center(s) of origin and diversity, flowering, pollen dispersal and longevity, sexual and vegetative reproduction, seed dispersal and dormancy, the existence and persistence of volunteers and feral plants, and the existence of weeds and their invasiveness potential); * Presentation of the most important CWR (information about their ploidy levels, diverse genomes, centers of origin, and geographic distribution); * Assessment of the crop's potential for hybridization with its wild relatives (relevant studies and literature); * Pollen flow studies related to pollen dispersal distances and hybridization rates (and recommended separation distances); * Overview summarizing the state of development of GM technology (global GM crop area, GM traits currently researched for the crop, and countries where GM varieties are grown commercially or in field trials). For some crops, information is provided on the extent of gene flow via seed exchange, the conservation status of CWR, and management recommendations to minimize gene flow in the field. At the end of each crop chapter, research gaps are identified and conclusions are drawn about the likelihood of gene flow and introgression.